The Role of Accounting Disclosure for Fixed Assets within The Framework of The International Accounting Standard (IAS16) In Improving the Quality of Financial Statements.: A Study of a Sample of Academics and Chartered Accountants Opinions in The City of Erbil - Azwar Anwar Osman; Parzheen shex mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Accounting disclosure of fixed assets is necessary to rely on accounting information by decision-makers inside and outside the economic unit. The International Accounting Standard (IAS 16) allowed the use of the recalibration approach to measure fixed assets. In order to achieve the objectives of the study and test its hypotheses, the questionnaire was relied upon, as the opinions of chartered accountants, computer controllers and academics in the city of Erbil were surveyed on the subject, and (214) individuals were tested. The study relied on the descriptive statistical analysis method and the analysis of the study variables. Testing its hypotheses using the statistical program for social sciences (SPSS). The study reached a set of conclusions, the most important of which is the accounting disclosure in the financial statements in accordance with the requirements of the International Accounting Standard (IAS 16) that serves the users of these lists because it indicates a fair presentation of the contents of these lists and also helps in understanding the financial performance, and all of this will have a significant impact on improving Users' decisions. Because the information contained in the financial statements is the main source for any decision taken by the user. As for the most important recommendations recommended by the study, it is necessary to prepare and present the financial statements in accordance with the requirements of the International Accounting Standard (IAS16) related to fixed assets, so that the information contained in the lists is with a high degree of accuracy, transparency and objectivity, which in turn helps users of the financial statements to make rational decisions.